Ultra-orphan diseases: a cross-sectional quantitative analysis of the natural history of isolated sulfite oxidase deficiency - Göde, Laura; Zielonka, Matthias; Garbade, Sven; Posset, Roland (PLOS ONE, 2025)
Objective Isolated sulfite oxidase deficiency (ISOD; OMIM #272300) is a devastating rare neurometabolic disorder due to biallelic pathogenic variants in the SUOX gene, that typically results in neonatal refractory epilepsy and progressive severe encephalopathy. Knowledge on the quantitative natural history of ISOD is limited and clinical outcome parameters for future clinical trials remain to be defined. Material and methods We performed a comprehensive analysis of published cases (N=74) with ISOD applying quantitative retrospective natural history modeling (QUARNAM). Main outcome parameters were age of disease onset, diagnostic delay and survival. Clinical characteristics and potential associations between biochemical parameters and clinical outcome (i.e. age of disease onset, survival) were explored. Results The median survival period of the study cohort was 60 months. ISOD typically presented shortly after birth with a median age of onset of 3 days. Median age at diagnosis was 10 months, leading to a substantial median diagnostic delay of 5.7 months. Homocysteine concentrations in plasma correlated with age of disease onset. An association of biochemical parameters of cysteine metabolism and survival could not be identified. Conclusion The present analysis describes long-term outcome measures adding to the quantitative understanding of the natural history of ISOD, which might be helpful in the planning of prospective clinical trials and potentially stimulate development of targeted therapies in the future.
Gesehen am 21.10.2025